Comparison of Sedentary Behaviors in Office Workers Using Sit-Stand Tables With and Without Semiautomated Position Changes. (August 2017) - Barbieri, Dechristian França; Srinivasan, Divya; Mathiassen, Svend Erik; Oliveira, Ana Beatriz
Objective: We compared usage patterns of two different electronically controlled sit-stand tables during a 2-month intervention period among office workers. Background: Office workers spend most of their working time sitting, which is likely detrimental to health. Although the introduction of sit-stand tables has been suggested as an effective intervention to decrease sitting time, limited evidence is available on usage patterns of sit-stand tables and whether patterns are influenced by table configuration. Method: Twelve workers were provided with standard sit-stand tables (nonautomated table group) and 12 with semiautomated sit-stand tables programmed to change table position according to a preset pattern, if the user agreed to the system-generated prompt (semiautomated table group). Table position was monitored continuously for 2 months after introducing the tables, as a proxy for sit-stand behavior. Results: On average, the table was in a "sit" position for 85% of the workday in both groups; this percentage did not change significantly during the 2-month period. Switches in table position from sit to stand were, however, more frequent in the semiautomated table group than in the nonautomated table group (0.65 vs. 0.29 hr -1 ; p = .001). Conclusion: Introducing a semiautomated sit-stand table appeared to be an attractive alternative to a standard sit-stand table, because it led to more posture variation. Application: A semiautomated sit-stand table may effectively contribute to making postures more variable among office workers and thus aid in alleviating negative health effects of extensive sitting.